ON LAND (WEALTH) DISTRIBUTION: A CULTURAL APPROACH TO JUSTICE IN INDONESIA - Suparjo, Suparjo (UI Scholars Hub, 2011)
This article re-examines the Indonesian land distribution policy in light of Pancasila , the five core values of the Indonesian constitution. Furthermore, the article also analyzes social problems in Indonesia from the legal and cultural point of view. Inspired by Javanese shadow puppet plays and Pancasila values, analysis shows that that land distribution policy in Indonesia does not support the goal of the country. The policy does not adhere to Pancasila values and the cultural values adopted by the Indonesian people. Hence I will try to give a recommendation for better regulation in land distribution. Evidences will be given to support the revision of land distribution policy in Indonesia by involving the academics through their researches and legal knowledge. This paper will also prove how doing so would resolve a lot of problems as poverty, unemployment matters, and social gaps; therefore social-economic justice can be promoted in accordance with the goals of the country.